Tea extracts inhibit the attachment of streptococci to oral/dental substrata by reducing hydrogen bonding energies. Issue 1 (2nd January 2022) - Wang, Yi; Samaranayake, Lakshman P.; Dykes, Gary A.
Abstract: Previous work in the authors' lab demonstrated that tea extracts significantly suppressed streptococcal colonization of abiotic substrata by coating the bacterial cell surfaces with tea components. In this study, the physico-chemical mechanisms by which the tea coating inhibits cellular attachment are demonstrated. The changes in the cell surface physico-chemical properties of streptococci, induced by tea extracts, were measured. Using these results, surface interaction energies were calculated between streptococcal cells and hard surfaces (glass, stainless steel, hydroxyapatite and titanium) within the cellular attachment system exploiting the extended Derjaguin-Landau-Verwey-Overbeek theory. The net energy outcomes were compared with experiment results of attachment assays to validate the predictability of the model. The results showed that the tea extracts inhibited the attachment of the bacteria by 11.1%–91.5%, and reduced the interaction energy by 15.4%–94.9%. It was also demonstrated that the abilities of the bacteria to attach to hard surfaces correlated well with their net interaction energies. The predominant interaction in the systems was found to be hydrogen bonding. In conclusion, tea extracts suppress streptococcal attachment to hard substrata by limiting the formation of hydrogen bonds. Graphical Abstract: UF0001